2013
DOI: 10.1136/heartjnl-2013-304082
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between cigarette smoking and peripheral arterial disease

Abstract: There is now substantial evidence of an association between active smoking and PAD. The magnitude of the association is greater than that reported for coronary heart disease. The risk is lower among ex-smokers but, nonetheless, significantly increased compared with never smokers. The results highlight the need for interventions both to encourage quitting among existing smokers and discourage commencement among never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
150
2
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(178 citation statements)
references
References 76 publications
14
150
2
12
Order By: Relevance
“…41 Globally, the most important risk factors are smoking, diabetes, hypertension, and high lowdensity lipoprotein-cholesterol levels, although the magnitude of these associations is higher in high-income countries than in low and middle-income countries. 6 Current evidence shows that the magnitude of the association between cigarette smoking and PAD is greater than that reported for coronary artery disease 42 and that secondhand smoke is an independent risk factor for PAD. 43 Moreover, there is a graded association between the number of modifiable risks factors and the prevalence of PAD, 22,24 and a long-term association between risk profiles at baseline and the risk of PAD after almost 40 years of followup.…”
Section: Control Of Risk Factors For Pad and The Need For Primary Prementioning
confidence: 91%
“…41 Globally, the most important risk factors are smoking, diabetes, hypertension, and high lowdensity lipoprotein-cholesterol levels, although the magnitude of these associations is higher in high-income countries than in low and middle-income countries. 6 Current evidence shows that the magnitude of the association between cigarette smoking and PAD is greater than that reported for coronary artery disease 42 and that secondhand smoke is an independent risk factor for PAD. 43 Moreover, there is a graded association between the number of modifiable risks factors and the prevalence of PAD, 22,24 and a long-term association between risk profiles at baseline and the risk of PAD after almost 40 years of followup.…”
Section: Control Of Risk Factors For Pad and The Need For Primary Prementioning
confidence: 91%
“…21 However, the subsequent report by the American Heart Association concluded that ABI≤0.9 remains the "most common and consensual threshold." 22 Similarly, in our recent review of published studies on active smoking and PAD 23 , ABPI<0.9 was the most commonly used definition. Participants were randomly selected from an association with branches throughout Guangzhou and should be reasonably representative of the relatively healthy general population in Guangzhou.…”
Section: Discussionmentioning
confidence: 99%
“…3 Claudication is a common clinical expression of PAD, and atherosclerosis is the main etiology. Smoking is one of the most potent risk factors for PAD, 4 and it is associated with an increased rate of mutagenesis and cancer. 5 Occurrence of V617FJAK2 mutation is increased (3.1%) in PAD patients compared with healthy subjects.…”
Section: Omarjee L Et Almentioning
confidence: 99%